Silver / bismuth double perovskite crystal and preparation method and application thereof

By designing silver/bismuth double perovskite crystals and utilizing the hydrogen bonding interaction between 3,3-difluoropiperidine cations and the inorganic layer to induce polar distortion of [AgBr]6 octahedron, we solved the problem of existing nonlinear optical materials. It solves the problems of humidity sensitivity and poor photoelectric properties, and achieves efficient second-order nonlinear optical effects and stability, which is suitable for the preparation of multifunctional integrated semiconductor materials and high-performance nonlinear optical devices.

CN119352167APending Publication Date: 2025-01-24JINLING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411466440.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing nonlinear optical materials have problems such as humidity sensitivity, high cost, difficult processing and poor photoelectric properties, which limit their application in the field of photoelectric response.

Method used

Designed a silver/钙bacarboskiite crystal (DFPD) 4AGBIBR8 · H2O), which interacts with the hydrogen bonds of inorganic layer through 3,3-dioflurathidine cation to induce the polarity of [AGBR] 6 eight-facial body Frequent crystals with excellent second -order non -linear optical properties.

Benefits of technology

The second -order non -linear optical coefficient at room temperature reaches more than 13 times that of potassium dihydrogen phosphate. It has excellent oxygen and moisture stability, and is suitable for the preparation of multi -functional integrated semiconductor materials and high -performance non -linear optical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005093468270000042
    Figure BDA0005093468270000042
  • Figure BDA0005093468270000051
    Figure BDA0005093468270000051
  • Figure HDA0005093468280000011
    Figure HDA0005093468280000011
Patent Text Reader

Abstract

The invention discloses a silver / bismuth double perovskite crystal and a preparation method and application thereof. The general molecular formula of the crystal is (DFPD) 4AgBiBr8. H2O (DFPD is a 3, 3-difluoropiperidine cation). The material has an excellent second-order nonlinear optical effect and good stability to oxygen and moisture; the material can be prepared into a photoelectric response device, and can be widely applied to the fields of green light / red light output obtained by frequency doubling (SHG), multi-photon microscopes, communication, terahertz detection, medical treatment, laser manufacturing and the like; the preparation method is simple, easy to obtain high-quality crystals and suitable for large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a silver / bismuth double perovskite crystal and a preparation method and application thereof, and in particular to a silver / bismuth double perovskite crystal with excellent second-order nonlinear optical effect and a preparation method and application thereof. Background Art

[0002] Nonlinear optical materials can provide tunable laser power through frequency conversion and are widely used in advanced optical and optoelectronic technologies such as laser manufacturing, lithography, multiphoton microscopy, communications, terahertz detection and medical treatment. Although nonlinear optical crystals such as potassium dihydrogen phosphate (KDP), lithium niobate (LN), potassium titanyl phosphate (KTP), barium metaborate (BBO), potassium fluoroborate beryllium (KBBF) and silver gallium sulfide (AGS) have promoted the development of photonics and optoelectronics, these materials have problems such as humidity sensitivity, high cost, difficult processing and poor optoelectronic properties, which hinder the miniaturization and integration of devices and limit their further application in the field of optoelectronic response.

[0003] At the same time, the second-order nonlinear optical effect of existing metal halide perovskite semiconductor materials is weak, especially the two-dimensional structure, whose second-order nonlinear optical coefficient is less than 1.3×KDP, and Pb 2+ Biological and environmental toxicity and Sn 2+ and Ge 2 + The instability towards oxygen also limits the application of these materials.

[0004] In addition, Hemamala I.Karunadasa et al. disclosed a layered halide double perovskite material (BA)4AgBiBr8 (BA = CH3(CH2)3NH3 + ), (Journal of the American Chemical Society, 2018, 140, 5235-5240). Studies have shown that although the double perovskite material uses silver and bismuth instead of lead, and the inorganic interlayers are arranged with n-butylamine cations, the (BA)4AgBiBr8 crystals are crystallized in a centrosymmetric space group, so they do not have a second-order nonlinear optical effect, which limits their application in the field of nonlinear optics. Summary of the invention

[0005] Purpose of the invention: The first purpose of the present invention is to provide a green and environmentally friendly silver / bismuth double perovskite crystal, the second purpose is to provide a method for preparing the crystal, and the third purpose is to provide an application of the crystal in the optoelectronic field.

[0006] Technical solution: The molecular formula of the silver / bismuth double perovskite crystal described in the present invention is (DFPD)4AgBiBr8·H2O, wherein DFPD is a 3,3-difluoropiperidinium cation; the space group of the crystal is P1, and the 3,3-difluoropiperidinium cation interacts with the NH···Br hydrogen bonds formed with the inorganic layer, and is arranged alternately upward and downward in adjacent inorganic sublattices, and the 3,3-difluoropiperidinium cations are connected together by van der Waals forces.

[0007] Preferably, the inorganic layer is formed by corner-sharing [AgBr]6 and [BiBr]6 octahedra.

[0008] In order to improve the performance of nonlinear optical crystals and expand their application scenarios, the present invention constructs a new type of lead-free metal halide perovskite material with excellent second-order nonlinear optical properties, which can be used as a multifunctional integrated semiconductor material.

[0009] In the crystal structure of the present invention, under the synergistic effect of water molecules, the 3,3-difluoropiperidinium cation induces a large polar distortion of the [AgBr]6 octahedron in the inorganic layer through a strong NH···Br hydrogen bond interaction. This polar distortion enables the crystal structure to have a large double harmonic generation (SHG) tensor, promoting the generation of second-order nonlinear optical effects. At the same time, under the synergistic effect of water molecules and the organic cation DFPD, the [AgBr]6 octahedron with a large structural distortion in the inorganic lattice can remain stable.

[0010] Preferably, the unit cell parameters of the silver / bismuth double perovskite crystal are

[0011] α=103.726(2)°, γ=90.085(2)°, β=103.280(2)°, Z=11,

[0012] Preferably, based on 2θ±0.02°, the silver / bismuth double perovskite crystal has characteristic peaks at 7.1°, 14.2°, 14.8°, 17.9°, 20.1°, 21.3°, 28.7°, and 36.0°.

[0013] Preferably, when the particle size of the silver / bismuth double perovskite crystal is in the range of 135 to 220 μm, the second-order nonlinear optical effect reaches a maximum value.

[0014] Preferably, the optical band gap value of the silver / bismuth double perovskite crystal is 2.72 eV.

[0015] Preferably, the silver / bismuth double perovskite nonlinear optical crystal has excellent light transmittance to light with a wavelength greater than 450 nm.

[0016] Preferably, the SHG effect intensity of the silver / bismuth double perovskite crystal in the particle size range of 135 to 170 μm is -0.276.

[0017] Preferably, the second-order nonlinear optical coefficient of the silver / bismuth double perovskite crystal is 12 to 13 times that of potassium dihydrogen phosphate.

[0018] Preferably, the SHG intensity of the silver / bismuth double perovskite crystal at 1064 nm increases with the increase of particle size and then tends to be constant, showing type I phase matching.

[0019] Preferably, the silver / bismuth double perovskite crystal has a stability of more than 12 months in an air environment with a relative humidity of 20% RH to 60% RH and a temperature of 270 to 313K.

[0020] Preferably, the laser damage threshold of the silver / bismuth double perovskite crystal is 235±5.1 MW / cm 2 .

[0021] The method for preparing the silver / bismuth double perovskite crystal of the present invention comprises the following steps:

[0022] (1) dissolving silver oxide and bismuth oxide in 47% by mass hydrobromic acid to prepare a hydrobromic acid solution containing silver ions and bismuth ions;

[0023] (2) dissolving 3,3-difluoropiperidine in 47% by mass hydrobromic acid to prepare a hydrobromic acid solution containing 3,3-difluoropiperidine;

[0024] (3) mixing the products of step (1) and step (2), and then stirring and heating until the mixture is dissolved to prepare a precursor solution;

[0025] (4) Cooling and crystallizing the precursor solution obtained in step (3) to obtain the silver / bismuth double perovskite crystal.

[0026] The chemical molar ratio of 3,3-difluoropiperidine to hydrobromic acid in step (2) is 1:3; the heating temperature in step (3) is 70-80°C; and the specific method for cooling and crystallizing in step (4) is to cool the precursor solution from 343K to 298K at a cooling rate of 1.5K / day, thereby obtaining the silver / bismuth double perovskite crystal.

[0027] The silver / bismuth double perovskite crystal of the present invention is used in the preparation of semiconductor materials.

[0028] Preferably, the semiconductor material described in the present invention is obtained by directly cutting the silver / bismuth double perovskite crystal described in the present invention.

[0029] Preferably, the silver / bismuth double perovskite crystals of the present invention are used in the preparation of high-performance nonlinear optical devices, specifically in the fields of advanced optics and optoelectronic technologies such as laser manufacturing, multiphoton microscopy, communications, terahertz detection, and medical treatment.

[0030] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0031] The silver / bismuth double perovskite single crystal designed by the present invention has excellent second-order nonlinear optical effect (the second-order nonlinear optical coefficient at room temperature is more than 13 times that of potassium dihydrogen phosphate) and good stability to oxygen and moisture; it can be prepared as a photoelectric response device and is widely used in the fields of double frequency generation (SHG) to obtain green light / red light output, multiphoton microscopy, communication, terahertz detection, medical field and laser manufacturing; the preparation method is simple, high-quality crystals are easily obtained, and it is suitable for large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The asymmetric unit structure diagram of silver / bismuth double perovskite crystal (DFPD) 4AgBiBr8·H2O;

[0033] Figure 2 The structural stacking diagram of silver / bismuth double perovskite crystal (DFPD) 4AgBiBr8·H2O;

[0034] Figure 3 It is the X-ray diffraction pattern of silver / bismuth double perovskite crystal (DFPD) 4AgBiBr8·H2O;

[0035] Figure 4 X-ray diffraction pattern of silver / bismuth double perovskite (DFPD) 4AgBiBr8·H2O for the stability test of moisture and oxygen;

[0036] Figure 5 This is the thermogravimetric analysis spectrum of silver / bismuth double perovskite crystal (DFPD) 4AgBiBr8·H2O;

[0037] Figure 6 Optical and theoretically calculated band gap diagrams of silver / bismuth double perovskite (DFPD) 4AgBiBr8·H2O;

[0038] Figure 7 The second-order nonlinear response and frequency-doubled-frequency spectrum effect diagram of silver / bismuth double perovskite crystal (DFPD) 4AgBiBr8·H2O;

[0039] Figure 8 Phase matching and birefringence performance diagram of silver / bismuth double perovskite crystal (DFPD) 4AgBiBr8·H2O;

[0040] Fig. 9This is the structure-property relationship diagram of silver / bismuth double perovskite crystal (DFPD) 4AgBiBr8·H2O. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described below in conjunction with embodiments.

[0042] The X-ray single crystal diffractometer was a Mini single crystal diffractometer from Rigaku, Japan; the X-ray diffractometer (PXRD) was a Rigaku SmartLab X-ray diffractometer; the thermogravimetric analyzer was an HTG-1 thermogravimetric analyzer from Beijing Hengjiu Experimental Equipment Co., Ltd.; the confocal scanning microscope was a commercial Witec alpha R300; the SHG module was assembled by a homemade scanning microscope and a Nd:YAG laser (wavelength of 1064nm, input pulse power of 400mV). Silver oxide, bismuth oxide, 3,3-difluoropiperidine and hydrobromic acid (47%) were all commercially available reagents.

[0043] Example 1: Preparation and structural characterization of silver / bismuth double perovskite nonlinear optical crystal (DFPD) 4AgBiBr8·H2O

[0044] 1. Crystal preparation

[0045] First, 2mmol silver oxide and 2mmol bismuth oxide were dissolved in 50mL HBr solution to obtain an HBr solution containing AgBr and BiBr3, and then 16mmol 3,3-difluoropiperidine was dissolved in 50mL HBr solution to obtain an HBr solution containing 3,3-difluoropiperidine; wherein the mass concentration of the HBr solution was 47%. The HBr solution containing AgBr and BiBr3 was mixed with the HBr solution containing 3,3-difluoropiperidine, and stirred continuously at 343K to obtain a clear solution, and crystals were obtained by solution cooling method, with a cooling rate of 1.5K / day to 298K, to obtain light yellow-green transparent block crystals with a yield of about 55%.

[0046] 2. Crystal structure characterization

[0047] A bulk single crystal of (DFPD)4AgBiBr8·H2O with a size of 0.2×0.2×0.2 mm was selected and subjected to X-ray single crystal diffractometer using a Rigaku (Mo) X-ray source. The crystal data at 293K were collected. The structure was solved directly using SHELXL-2018 software, all non-hydrogen atoms were anisotropically refined, and all hydrogen atoms were added by theoretical hydrogenation. The crystallographic data of (DFPD) 4AgBiBr8·H2O are shown in Table 1.

[0048] Table 1 Crystal structure data

[0049]

[0050]

[0051] a R1=Σ||F o |-|F c || / |F o |;

[0052] b wR2=[Σw(F o 2 -F c 2 ) 2 ] / Σw(F o 2 ) 2 ] 1 / 2 ;

[0053] c Maximum and minimum residual electron density.

[0054] Figure 1 It is the smallest asymmetric unit of the (DFPD)4AgBiBr8·H2O crystal structure. Figure 2 This is the structure diagram of (DFPD)4AgBiBr8·H2O crystal. Figure 2 In the structure, the corner-sharing [AgBr]6 and [BiBr]6 octahedra form inorganic layers, and DFPD is used as a spacer cation to be oriented and arranged between the inorganic layers in an alternating upward and downward manner, forming a two-dimensional layered stacking structure in space. Under the synergistic effect of water molecules and organic cation DFPD, the [AgBr]6 octahedron with large structural distortion maintains structural stability.

[0055] 3. Evaluation of crystal phase purity

[0056] The crystal (DFPD) 4AgBiBr8·H2O sample was collected on an X-ray diffractometer (PXRD). The test angle range was 0° to 50°, and the test rate was 20° / min. The XRD spectra of the data obtained by X-ray diffraction were compared with those obtained by room temperature single crystal structure simulation. The obtained crystal was pure phase ( Figure 3 a), and the dominant growth orientation of its single crystal is (001) direction ( Figure 3 b).

[0057] 4. Evaluation of crystal stability to moisture and oxygen

[0058] The crystalline (DFPD) 4AgBiBr8·H2O sample placed in air with a relative humidity of 60% for 12 months was ground into powder, and the diffraction data were collected on an X-ray diffractometer (PXRD). The diffraction data were compared with the single crystal structure simulation data and the PXRD data of the newly prepared crystal, and it was found that it has excellent resistance to moisture and oxygen ( Figure 4 ).

[0059] 5. Evaluation of thermal stability of crystals

[0060] The temperature stability of the (DFPD) 4AgBiBr8·H2O crystal sample was analyzed by thermogravimetric analysis. It began to lose the crystal water in the unit cell at 352K, and the structure changed ( Figure 5 a); at the same time from Figure 5 In b, we can see that the intensity of the SHG effect of the crystal remains stable below 352K, and begins to decrease above 352K. As the temperature rises further to 407K, the crystal completely loses its crystalline water, and the SHG signal intensity also becomes zero, showing the properties of an optical switch ( Figure 5 ).

[0061] Example 2: Optical band gap and second-order nonlinear optical effect evaluation of silver / bismuth double perovskite nonlinear optical crystal (DFPD) 4AgBiBr8·H2O crystal

[0062] 1. Evaluation of the optical band gap performance of crystals

[0063] The light transmittance performance was tested using UV-visible reflectance spectroscopy and first-principles calculations (DFT). The results are as follows: Figure 6 shown. Figure 6 a is the semiconductor band gap of (DFPD)4AgBiBr8·H2O sample calculated from UV-visible reflection spectrum and Kubelka-Munk equation, and the optical band gap is 2.72eV. The theoretical value calculated by DFT is 3.23eV, and the band gap values ​​obtained by experiment and theoretical calculation are in the same order of magnitude ( Figure 6 b). The crystal has good transmittance to light with wavelength greater than 450nm.

[0064] 2. Evaluation of the second-order nonlinear optical properties of crystals

[0065] Second harmonic generation (SHG) spectra were obtained using a commercial confocal scanning microscope (Witec alphaR300) combined with a SHG module. Figure 7 a It can be seen that the 1064nm light becomes light with a wavelength of 532nm after passing through the crystal, and the double frequency (SHG) obtains green light / red light output.

[0066] The second harmonic generation of (DFPD) 4AgBiBr8·H2O crystal sample and KDP crystal sample was detected by Kurt Perry method under reflection geometry conditions using a self-made scanning microscope and Nd:YAG laser (wavelength of 1064nm, input pulse power of 400mV). In the particle size range of 135-170μm, the SHG effect intensity of KDP is -0.021, and the SHG effect intensity of double perovskite nonlinear crystal is -0.276, which is 13.14 times that of KDP ( Figure 7 b) In addition, Figure 8 a It can be seen that the SHG intensity at 1064nm increases with the increase of particle size and then tends to be constant, indicating that the material is type I phase matching. Refractive index dispersion curve ( Figure 8 b) shows moderate birefringence (Δn = 0.095@532nm and 0.057@1064nm), confirming the phase matching in the experiment ( Figure 8 a). Therefore, this material has good application prospects in laser manufacturing and other fields.

[0067] 3. Evaluation of laser damage threshold of crystal

[0068] The laser damage threshold (LIDT) of (DFPD) 4AgBiBr8·H2O crystal samples was measured using a Q-switched pulsed laser. The particle size range of the tested samples was 150-220μm, the laser wavelength was 1064nm, the pulse duration was 10ns, the pulse frequency was 1Hz, and the spot area focused on the sample was 2.01mm 2 During the measurement, the laser emission energy gradually increased. When the sample turned black under laser irradiation, the LIDT range of the sample was 229.2-241.3 MW / cm 2 (235±5.1MW / cm 2 ).

[0069] 4. Relationship between the second-order nonlinear optical effect of crystals and their structure

[0070] The second-order nonlinear optical sensitivity of (DFPD)4AgBiBr8·H2O was evaluated by theoretical calculations. Under the constraints of Kleinman symmetry and space group (P1), there are 10 independent non-zero SHG tensors, among which the SHG tensor d 11 Maximum (4.99pm / V), about 12.8 times that of KDP [d 36 (KDP) = 0.39 pm / V], which is consistent with the experimental data. 11 The SHG-weighted electron density (SHG density) is analyzed to further reveal its cause from the perspective of electronic structure ( Fig. 9 a~ Fig. 9 d). In the conduction band (CB), the unoccupied orbitals of Bi-6p play an important role in the SHG effect, with Ag-5s and Br-4p also contributing to a small extent ( Fig. 9 a and 9c). In the valence band (VB), the SHG effect mainly originates from the Br-4p non-bonding state in [AgBr6] and the full occupation of the Ag-4d electronic state ( Fig. 9 b and Fig. 9 d). Numerically, the SHG contribution percentages of [AgBr6], [BiBr6], H2O and DFPD are 69.9%, 29.9%, 0.1% and 0.1%, respectively ( Fig. 9 e), indicating

[0071] The strong SHG response of (DFPD)4AgBiBr8·H2O is derived from the water molecules and organic cations in the lattice.

[0072] The synergistic effect of the highly distorted [AgBr6] and [BiBr6] octahedra that are synergistically stabilized by DFPD.

Claims

1. A silver / bismuth double perovskite crystal, characterized in that: The molecular formula is (DFPD)4AgBiBr8·H2O, wherein DFPD is a 3,3-difluoropiperidinium cation; the space group of the crystal is P1, and the 3,3-difluoropiperidinium cation interacts with the NH···Br hydrogen bonds formed with the inorganic layer, and is arranged alternately upward and downward in adjacent inorganic sublattices, and the 3,3-difluoropiperidinium cations are connected together by weak intermolecular interactions.

2. The silver / bismuth double perovskite crystal according to claim 1, characterized in that The inorganic layer is formed by corner-sharing [AgBr]6 and [BiBr]6 octahedra.

3. The silver / bismuth double perovskite crystal according to claim 1, characterized in that: The unit cell parameters are α=103.726(2)°, γ=90.085(2)°, β=103.280(2)°, Z=11, 4. The silver / bismuth double perovskite crystal according to claim 1, characterized in that: In terms of 2θ±0.02°, it has characteristic peaks at 7.1°, 14.2°, 14.8°, 17.9°, 20.1°, 21.3°, 28.7°, and 36.0°.

5. The silver / bismuth double perovskite crystal according to claim 1, characterized in that: The particle size range is 135~220μm.

6. The silver / bismuth double perovskite crystal according to claim 1, characterized in that: The optical band gap value is 2.72 eV.

7. The silver / bismuth double perovskite crystal according to claim 1, characterized in that: The SHG effect intensity in the particle size range of 135 to 170 μm is -0.

276.

8. The silver / bismuth double perovskite crystal according to claim 1, characterized in that Laser damage threshold is 235.0±5.1MW / cm 2 .

9. A method for preparing the silver / bismuth double perovskite crystal according to claim 1, characterized in that: The following steps are involved: (1) dissolving silver oxide and bismuth oxide in hydrobromic acid to prepare a hydrobromic acid solution containing silver ions and bismuth ions; (2) dissolving 3,3-difluoropiperidine in hydrobromic acid to prepare a hydrobromide solution containing 3,3-difluoropiperidine; (3) mixing the products of step (1) and step (2), and then stirring and heating until the mixture is dissolved to prepare a precursor solution; (4) Cooling and crystallizing the precursor solution obtained in step (3) to obtain the silver / bismuth double perovskite crystal.

10. Use of the silver / bismuth double perovskite crystal according to claim 1 in preparing semiconductor materials.